Improving The Cognitive Skills Of 4–5-Year-Old Children In Introducing Science Through Experimental Methods In State Children's Preschool In The 2024/2025 Academic Year - Aeni, Idayatul; Sumiadi, Raden; Ramzi, Muhajirin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
To analyze how to improve children's cognitive development (introduction to science) through experimental methods in early childhood education for the 2024/2025 school year. With the formulation of the problem How to improve children's cognitive development (introduction to science) through experimental methods in PAUD Anak Negeri for the 2024/2025 school year?. This research is a class action research (PTK) with a research model from the design of Kemmis and Mc Taggart which consists of four main activities, namely planning, implementation, observation or observation and reflection. This research was carried out with II cycles, each cycle consisted of four meetings. The subjects of this study are class A children aged 4-5 years in PAUD Anak Negeri which totals 13 children. The results of the study showed that in the pre-action consisting of 13 children before carrying out learning activities using the color mixing experiment method and the rainbow walking experiment that reached the criteria of developing very well (BSB) there were no or 0 children, 6 children achieved the development of the keriteria as expected (BSH), 6 children reached the keriteria began to develop (MB) and 2 children who were still in the keriteria had not developed (BB) so that the completeness obtained in Actions in this pre-cycle reached 23.07%. The achievement of children in the first cycle of 13 children after the action of the researcher using the color mixing experiment method increased to 61.4% then from the action in the first cycle the completeness achieved was 61.5%. Then continued in cycle II out of 13 children, there were 10 children who achieved very good ketal cariteria (BSB), 3 children were in the chiriteria developing according to expectations (BSH), so the completeness achieved in the action in cycle II reached 84.6% completeness. Therefore, from the results that have been seen from cycle II, namely that it has reached the limit of completeness planned by the researcher, therefore the research activity was completed at the cycle II stage because it has been said to be successful in research activities using experimental methods to improve the cognitive of children aged 4-5 years in the introduction of science in PAUD Anak Negara.